Effect of peer support interventions on cardiovascular disease risk factors in adults with diabetes: a systematic review and meta-analysis - Sonal J. Patil; Todd Ruppar; Richelle J. Koopman; Erik J. Lindbloom; Susan G. Elliott; David R. Mehr; Vicki S. Conn (BMC, 2018)
Abstract Background Peer support by persons affected with diabetes improves peer supporter's diabetes self-management skills. Peer support interventions by individuals who have diabetes or are affected by diabetes have been shown to improve glycemic control; however, its effects on other cardiovascular disease risk factors in adults with diabetes are unknown. We aimed to estimate the effect of peer support interventions on cardiovascular disease risk factors other than glycemic control in adults with diabetes. Methods We conducted a systematic review and meta-analysis of randomized controlled trials comparing peer support interventions to a control condition in adults affected by diabetes that measured any cardiovascular disease risk factors [Body Mass Index, smoking, diet, physical activity, cholesterol level, glucose control and blood pressure]. Quality was assessed by Cochrane's risk of bias tool. We calculated standardized mean difference effect sizes using random effects models. Results We retrieved 438 citations from multiple databases including OVID MEDLINE, Cochrane database and Scopus, and author searches. Of 233 abstracts reviewed, 16 articles met inclusion criteria. A random effects model in a total of 3243 participants showed a positive effect of peer support interventions on systolic BP with a pooled effect size of 2.07 mmHg (CI 0.35 mmHg to 3.79 mmHg, p = 0.02); baseline pooled systolic blood pressure was 137 mmHg. There was a non-significant effect of peer support interventions on diastolic blood pressure, cholesterol, body mass index, diet and physical activity. Cardiovascular disease risk factors other than glycemic control outcomes were secondary outcomes in most studies and baseline values were normal or mildly elevated. Only one study reported smoking outcomes. Conclusions We found a small (2 mmHg) positive effect of peer support interventions on systolic blood pressure in adults with diabetes whose baseline blood pressure was on average minimally elevated. Additional studies need to be conducted to further understand the effect of peer support interventions on high-risk cardiovascular disease risk factors in adults with diabetes.